Violence in love relationships and domestic violence: Convergences and divergences. Reflections for a future discussion - Sanhueza Morales, Tatiana (Última Década, 2019)
The present article results from a bibliographical review of a number of particular aspects of violence in love relationships of teenagers and in domestic violence in adult couples, displaying relevant results in the context of a wider exploratory investigation. Opinions from 48 Chilean teenagers, of both sexes and from different social stratum, participating in discussion groups are gathered. Both the empirical results obtained and the reviewed literature are sufficient to argue the presence of a different phenomenon that set theoretical and practical challenges.